The Effect of Faculty Research on Student Learning in College. (May 2022) - Loyalka, Prashant; Shi, Zhaolei; Li, Guirong; Kardanova, Elena; Chirikov, Igor; Yu, Ningning; Hu, Shangfeng; Wang, Huan; Ma, Liping; Guo, Fei; Liu, Ou Lydia; Bhuradia, Ashutosh; et al.
Whether faculty research affects college student learning has long been the subject of debate. Previous studies use subjective measures of student learning; focus on correlation rather than causation; and typically focus on one college, thus lacking generalizability. Using unique, large-scale survey and assessment data that we collected from nationally representative samples of STEM undergraduates in China, India, and Russia, as well as a causal identification strategy that accounts for differential sorting of students to faculty, we present generalizable estimates of the effect of faculty research on objective, standardized measures of student learning. Results show that faculty research has a negative effect on student learning, suggesting direct trade-offs between the university's dual mission of producing research and learning.